EinFach Logistik. Nauczanie niemieckiego języka logistyki – źródła inspiracji oraz nowe wyzwania dla logistyków i germanistów - Górski, Karol; Janiak, Tomasz (Investigationes Linguisticae, 2016)
Driven by sociolinguistic inspirations, the authors make an attempt to assess the teaching of German logistics language in Poland for professional purposes against a broadly understood logistic education and emphasize the aspect of close correlation of the linguistic training outcome with the labor market demand. The intention of the authors is to highlight an important component of the education environment, namely the need to interrelate the proper content-oriented knowledge with linguistic skills of the logistic secondary school students and the university level students dealing with logistics.